Improving charge separation efficiency and piezo-photodegradation properties in Na0.5Bi0.5TiO3 via lattice engineering. Issue 19 (1st October 2022) - Ji, Jiamin; Pu, Yongping; Ouyang, Tao; Chang, Liangliang; Zhou, Shiyu; Zhang, Lei
Abstract: Low bulk charge separation efficiency restricts the number of reactive oxygen species that react in the surface of photocatalysts, and deteriorates the photocatalytic performance. To overcome this obstacle, Na0.5 Bi0.5 TiO3 was selected and trace (Bi0.5 Na0.5 ) 2+ was substituted by Ba 2+ via the molten salt method. Ba 2+ expanded the volume of oxygen octahedra and extended the offset of Ti 4+ ions from the oxygen octahedral centre. Thus, intensive dipole-dipole interaction was brought and the ferroelectric polarization was boosted. With the aid of the powerful driving force, the photocatalytic degradation rate reached the maximum ( k = 0.037 min −1 ) when x = 0.02 (NBBT2), which was 5 times than pristine Na0.5 Bi0.5 TiO3 . At the same time, NBBT2 unveiled unique piezo-photocatalytic performance and cycling stability towards RhB, tetracycline and ciprofloxacin. This work takes advantage of lattice engineering to boost the ferroelectric polarization and ultrasonic vibration to separate the bulk charges and enhance the catalytic efficiency.